Oil Politics and Governance: Emerging Socio-Economic Trends in Nigerian States - Alaye, Adekunle (Acta Universitatis Danubius. Juridica, 2024)
In Nigeria, the relationship between oil and governance is a complex issue that needs close examination. Rather than serving as a driving force for fair growth, the country’s enormous oil riches has contributed to ongoing socioeconomic inequality, corruption, and environmental damage. The mishandling of oil flows is the main component of this problem. Because of the resulting enthusiasm, the advantages of this recurring value are not sufficiently channeled to ensure the sustainability of development initiatives. The insidious influence of corruption within the oil sector is exacerbating the governance crisis, with bots, malfeasance and fraudulent activities deeply unleashed. Public confidence in government institutions is damaged as a result, which has a significant impact on the political and socioeconomic structures of the nation. The study aims to explore the deeper connections between the petroleum sector and Nigerian governance by identifying and critically analyzing the underlying causes of mismanagement, corruption, and environmental degradation. The research requires a thorough examination of the structural and systemic issues that contribute to corruption in the oil and gas industry in order to formulate robust anti-corruption strategies. It is imperative to reassess policies to ensure the responsible extraction and management of petroleum resources. Thus, the study aimed to provide all-encompassing solutions that would eventually support evidence-based policy.